Plasma homocysteine concentrationand MTHFR C677T polymorphism are related to ischemic stroke - ZHANG Yuchao, XIE Mingzhang, ZHAO Mengmeng, ZHOU Xiaochun, YANG Chenyan, LIU Yanxuan (Jichu yixue yu linchuang)
Objective To investigate the correlation of plasma homocysteine (Hcy) level and the polymorphisms of its key metabolic enzymes methylenetetrahy-drofolate reductase (MTHFR) gene with ischemic stroke (IS). Methods A total of 310 patients with IS were enrolled as the case group and 330 healthy subjects during the same period were selected as the control group. Plasma Hcy concentration was detected by enzyme cycling method, and the real-time fluorescent quantitative PCR (RT-qPCR) was used to detecte the genotypes of MTHFR C677T. Results The frequencies of TT genotype (36.13%),CT genotype (10.00%) and T allele (28.06%) of MTHFR gene C677T locus in stroke patients were significantly higher than that in control group (P＜0.05).The frequency of the TT genotype was significantly higher in IS group compared to control group, indicating a recessive mode of inheritance(P＜0.05); In the dominant mode of inheritance, the frequency of CT+TT genotype in IS group wasalso significantly higher than that in control group(P＜0.05); The plasma Hay concentration of MTHFR C677T genotype TT, CT and CC patients was statistically different (P＜0.05), which were (20.91±6.78) μmol/L(17.20±5.39)μmol/L, (14.35±4.32)μmol/L, respectively; The area under the ROC curve (AUC) of plasma total Hcy level was 0.610 (95% CI: 0.566 ~ 0.653, P＜0.001). It indicated that it might play an important role in predicting the risk of suffering from IS. Multivariate Logistic regression analysis showed that plasma Hcy level and MTHFR C677T gene polymorphism were important risk factors of IS. Conclusions Elevated plasma Hcy level is associated with IS, and the synergistic effect of elevated Hcy level and MTHFR C677T gene mutation may increase the risk of IS.